THE EFFECT OF MANGROVE LEAF EXTRACT (AVICENNIA MARINA) FEED ON GROWTH AND SURVIVAL RATE OF CLIMBING PERCH (ANABAS TESTUDINEUS) - Akbar J.; Redha El; Fauzana N.A. (Russian Journal of Agricultural and Socio-Economic Sciences)
The climbing perch (Anabas testudineus) is a type of local fish that is popular by the people of South Kalimantan and has high economic value. One of the factors that influence the growth of climbing perch is feed. One of the natural ingredients that can be used to increase fish growth is mangrove leaf extract. The purpose of this study was to determine the effect of adding of Avicennia marina leaf extract to increase the growth and survival of climbing perch. The study used a completely randomized design (CRD) with 4 (four) treatments, namely treatment P1 feeding with no addition of leaf extracts of A. marina as control, treatment P2 feeding with addition of leaf extracts of A. marina as much as 100 ppm/kg of feed, P3 treatment 200 ppm/kg of feed and P4 treatment of 300 ppm/kg of feed. The parameters observed were absolute weight growth, relative growth rate, survival, feed conversion, feed efficiency, and water quality. Climbing perch were fed 5% of fish biomass per day and the frequency of feeding was 2 times a day for 45 days. The results of the study showed that the climbing perch fed with the addition of A. maria leaf extract 300 ppm/kg of feed resulted in weight growth, relative growth rate, feed conversion, feed efficiency in the P4 treatment of 4.71 g, 71.36%, 1.32, 112.59% and SR 100% respectively. Water quality parameters were still in reasonable conditions, ideal for the growth of climbing perch kept during the study.